PENINGKATAN HASIL BELAJAR PENGUKURAN LUAS DAN VOLUME MENGGUNAKAN MODEL PROJECT BASED LEARNING KELAS IV SD NEGERI 29 DADOK TUNGGUL HITAM KOTA PADANG - Yulius, Diana; Zainil, Melva; Nisa, Sahrun; Ningsih, Yarisda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Low academic achievement in mathematics, specifically on the topic of area and volume measurement among fourth-grade pupils at SDN 29 Dadok Tunggul Hitam, Padang City, provided the background for this study. Preliminary observations revealed that learning was not fully student-centered and Project Based Learning (PjBL) had not been implemented for this material. This classroom action research aimed to describe the planning, implementation, and improvement of pupils' learning outcomes using the PjBL model. Combining qualitative and quantitative approaches, the study involved 28 fourth-grade pupils (17 males and 11 females) across two cycles. Data were gathered through non-test and test instruments. Results showed that teaching module quality increased from 87.5% (Good) in Cycle I to 95.8% (Very Good) in Cycle II. Teacher activity implementation increased from 90.6% (Good) to 96.8% (Very Good), and student activity rose from 87.5% (Good) to 93.7% (Very Good). Pupils' average affective scores improved from 73.21% to 83.25%, psychomotor scores from 65.18% to 83.33%, cognitive scores from 76.78% to 85.71%, and project evaluation scores from 66.07% to 85.27%. It is concluded that the PjBL model effectively improves learning outcomes in area and volume measurement.